Kritik Terhadap Metode Konseling Motivational Interviewing - Nurul Ahwat Rantekata; Nurjannah Nurjannah (Islamika : Jurnal Ilmu-Ilmu Keislaman, 2022)
The development of counseling theory can be seen from the findings made by researchers who I am to be able to solve human problems in accordance with the times. Ranging from classical to contemporary theory continues to add to the list of discoveries made by thinkers in the field of counseling. Criticisms and inputs made by current researchers on the theories of previous scientists are a scientific activity that has a positive impact on the development of science. This study aims to develop a contemporary counseling method, namely Motivational Interviewing from William R. Miller. This research method uses a literature review by reviewing various literatures including literature found in libraries, google books, and google scholar. So that the motivational counseling interviewing counseling method can be developed and relate it to the Islamic approach with the concept of the piety model from Syafiq Falah Alwaney’s theory then an effort and tawakkal approach is added to perfect the concept of developing this counseling method. We hope that by developing a contemporary counseling method from the West, namely Motivational Interviewing using the Islamic approach, the Takwa, Ikhtiar, and Tawakkal model or abbreviated as MIMTIT can be applied by counselors in the counseling process so that the counselee is able to make efforts to change with the motivation that has been found in him, then put his trust in Allah SWT. to the provisions that will occur during the transformation of the changes made.